The Implementation of Canvas Model in Plan Determination of Swallow Nest Business Management - Suwandi Suwandi; Jaka Waskito (Budapest International Research and Critics University, 2022)
This study aims to determine whether the swallow nest business planning swallow using the Business Model Canvas (BMC) can find out how the business is currently being carried out. This research was conducted in Pangkalan Bun, Central Kalimantan. Researchers can also describe and develop BMC using SWOT analysis utilizing the nine elements of BMC introduced by Alexander Osterwalder and Yveus Pigneur. This research is a descriptive qualitative research. This research was conducted on Pak Haji Huda's swallow nest business, located in Kumai, West Kotawaringin Regency, Central Kalimantan. This research was conducted in 2019. The result of this research is that there is strength in customer segments by having customers who are well segmented because they already have cooperation, value propositions with customers who are satisfied with the products and services provided by the swallow nest entrepreneur. Channels with sales to collectors or factories make swallow nests sure to always be sold, thus, there are no unsold products.